Extraction of bioactive compounds from pecan nutshell: an added-value and low-cost alternative for an industrial waste - Cardona Jiménez, Miguel Esteban; Gabilondo, Julieta; Bodoira, Romina Mariana; Agudelo Laverde, Lina Marcela (Elsevier, 2024)
The pecan nutshell [Carya illinoinensis (Wangenh) C. Koch] (PNS) is a source of bioactives with important beneficial properties for the human health. PNS represents between 40–50 % of total mass of the nut, resulting as waste without any added value for the food industry. Even though a variety of methods were already developed for bioactive extraction from this waste, unconventional methodologies, or those which apart from green chemistry principles, were discarded considering the cost of production, the sustainable development goals of United Nations and the feasibility of real inclusion of the technology in the food chain. Then, to add-value to this waste, a low-cost, green and easy-scalable extraction methodology was developed based on the determination of seven relevant factors by means of a factorial design and a Response Surface Methodology, allowing the extraction of bioactives with antioxidant capacity. The pecan nutshell extract had a high concentration of phenolic compounds (166 mg gallic acid equivalents-GAE/g dry weight-dw), flavonoids (90 mg catechin equivalent-CE/g dw) and condensed tannins (189 mg CE/g dw) −related also to the polymeric color (74.6 %)-, with high antioxidant capacities of ABTS+. radical inhibition (3665 µmol Trolox Equivalent-TE/g dw) and of iron reduction (1305 µmol TE/g dw). Several compounds associated with these determinations were identified by HPLC-ESI-MS/MS, such as [Epi]catechin-[Epi]catechin-[Epi]gallocatechin, myricetin, dihydroquercetins, dimers A and B of protoanthocyanidins, ellagitannins and ellagic acid derivatives. Hence, through the methodology developed here, we obtained a phenolic rich extract with possible benefits for human health, and of high industrial scalability for this co-product transformation.